Polymerization shrinkage, modulus, and shrinkage stress related to tooth-restoration interfacial debonding in bulk-fill composites. Issue 4 (April 2015) - Kim, Ryan Jin-Young; Kim, Yu-Jin; Choi, Nak-Sam; Lee, In-Bog
Abstract: Objectives: The aim of the present study was to measure the polymerization shrinkage, modulus, and shrinkage stress of bulk-fill and conventional composites during polymerization and to investigate the relationship between tooth-composite interfacial debonding and shrinkage stress of the composites. Methods: Polymerization shrinkage, dynamic modulus, and shrinkage stress of two high-viscosity bulk-fill (SonicFill (SF)/Tetric N-Ceram Bulk-Fill (TNB)) and two low-viscosity bulk-fill composites (Filtek Bulk-Fill (FB)/SureFil SDR Flow (SDR)) as well as one high-viscosity conventional (Filtek Z250 (Z250)) and one low-viscosity conventional composite (Filtek Z350 XT Flowable (Z350F)) were measured using custom-made instruments. Acoustic emission (AE) analysis was performed to evaluate the tooth-composite interfacial debonding during polymerization of the composites in Class 1 cavities on extracted third molars. Results: The low-viscosity composites exhibited higher shrinkage and lower modulus than the high-viscosity composites. Polymerization shrinkage at 10 min ranged between 2.05% (SF) and 3.53% (Z350F). Polymerization shrinkage stress values at 10 min ranged between 1.68 MPa (SDR) and 3.51 MPa (Z350F). The number of AE events was highest in Z350F and lowest in SDR. Conclusions: Composites that exhibited greater polymerization shrinkage stress generated more tooth-composite interfacial debonding. In contrast to similar outcomes among the high-viscosity composites (conventional: Z250, bulk-fill: TNB and SF), the low-viscosity bulk-fill composites (FB and SDR) demonstrated better results in terms of polymerization shrinkage stress and tooth-composite interfacial debonding than did the low-viscosity conventional composite (Z350F). Clinical significance: Despite the better performance by some of the bulk-fill composites, clinicians should be aware that the bulk-fill composites are not perfect substitutes for conventional composites.